2020
DOI: 10.3389/fphar.2020.00482
|View full text |Cite
|
Sign up to set email alerts
|

Safflower Yellow and Its Main Component HSYA Alleviate Diet-Induced Obesity in Mice: Possible Involvement of the Increased Antioxidant Enzymes in Liver and Adipose Tissue

Abstract: Purpose: Oxidative stress plays an important role in the pathogenesis of obesity and its associated disorders. Safflower yellow (SY) and hydroxysafflor yellow A (HSYA), the natural compounds isolated from Carthamus tinctorius L., has been found to possess antioxidative and anti-obesity properties. The purpose of the present study is to investigate whether SY and its main component HSYA alleviate obesity by the antioxidant effects. Methods: Diet-induced obese (DIO) mice were treated with 200 mg/kg/d SY or HSYA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The murine 3T3-L1 preadipocytes were cultured according to protocol previously implemented in our lab ( Zhu et al, 2013 ; Zhu et al, 2015 ; Yan et al, 2020 ). Briefly, 3T3-L1 cells were cultured in DMEM/F12 medium supplemented with 10% FBS and 1% antibiotics (100 U/ml penicillin and 100 U/ml streptomycin) in CO 2 incubator (Thermo, United States).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The murine 3T3-L1 preadipocytes were cultured according to protocol previously implemented in our lab ( Zhu et al, 2013 ; Zhu et al, 2015 ; Yan et al, 2020 ). Briefly, 3T3-L1 cells were cultured in DMEM/F12 medium supplemented with 10% FBS and 1% antibiotics (100 U/ml penicillin and 100 U/ml streptomycin) in CO 2 incubator (Thermo, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation of 3T3-L1 preadipocytes and human primary preadipocytes were conducted in our lab as described previously ( Zhu et al, 2013 ; Zhu et al, 2015 ; Miao et al, 2019 ; Yan et al, 2020 ). Briefly, 2 days after preadipocytes achieved confluence (designated as day 0), differentiation was induced by culturing cells with 10% FBS DMEM/F12 medium (for 3T3-L1 preadipocytes) or basal culture medium (for human primary preadipocytes) supplemented 1 mg/ml insulin, 50 mM 3-isobutyl-1-methylxanthine (IBMX) and 10 mM dexamethasone (Gibco BRL, Grand Island, United States) for 4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further pharmacological studies demonstrated that the polyacetylenes from C. tinctorius inhibited LPS-induced NO (nitric oxide) release, showing its potential as an agent for treating inflammatory diseases [ 6 ]. Recent studies have shown that extracts of safflower inhibited the adipogenesis of 3T3-L1 preadipocytes and alleviated high-fat diet-induced obesity in mice [ 7 , 8 , 9 , 10 ]. In addition, treatment with safflower extracts improved metabolic parameters, such as glucose metabolism and lipid profiles, in mice with diet-induced obesity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that extracts of safflower inhibited the adipogenesis of 3T3-L1 preadipocytes and alleviated high-fat diet-induced obesity in mice [ 7 , 8 , 9 , 10 ]. In addition, treatment with safflower extracts improved metabolic parameters, such as glucose metabolism and lipid profiles, in mice with diet-induced obesity [ 9 , 10 ]. Despite numerous evidences showing the beneficial effects of safflower on metabolism, the exact compounds responsible for the action and the mechanisms underlying their action remain undiscovered.…”
Section: Introductionmentioning
confidence: 99%